Genome-wide identification of the wall-associated kinase gene family and their expression patterns under various abiotic stresses in soybean (Glycine max (L.) Merr) - Li, Xiangnan; Qi, Sifei; Meng, Lingzhi; Su, Peisen; Sun, Yongwang; Li, Nan; Wang, Dan; Fan, Yinglun; Song, Yong (Frontiers in Plant Science, 2025)
The wall-associated kinase (WAK) gene family encodes functional cell wall-related proteins. These genes are widely presented in plants and serve as the receptors of plant cell membranes, which perceive the external environment changes and activate signaling pathways to participate in plant growth, development, defense, and stress response. However, the WAK gene family and the encoded proteins in soybean (Glycine max (L.) Merr) have not been systematically investigated. In this study, the soybean WAK genes (GmWAK) were identified based on genome-wide sequence information, the basic characteristics, chromosome location, gene replication, expression pattern, and responses to stress were comprehensively analyzed. A total of 74 GmWAK genes were identified and mapped to 19 different chromosomes in the soybean genome. Seventy-four GmWAK genes were divided into four groups, and GmWAK genes in the same group shared similar gene structures and conserved motifs. Thirty-seven duplicate pairs were identified in 74 GmWAK genes. Segmental duplication (SD) was critical in soybean WAK gene family expansion, and purification selection occurred during evolution. The promoter cis-element analysis displayed many hormone- and stress-related response elements in the promoter regions of GmWAK genes. GmWAK genes were diversely expressed in different organs and tissues, with most actively responding to cold, heat, salt, drought, and heavy metal stresses, suggesting that GmWAK genes could exhibit relevant roles in various bioprocesses.